Analysis of the market of meat products in Ukraine - Artem Antoniv; Leonora Adamchuk; Eva Ivanišová; Róbert Chlebo; Erkan Topal (Тваринництво та технології харчових продуктів, 2023)
Meat and meat products are among the main products of the human diet, which contain the essential nutrients, biological, macro and microelements that are important for the full functioning of the human body. Due to the significant environmental impact associated with industrial meat production, combined with the ever-growing world population, it is important to investigate the current state and production of the meat industry. The purpose of the study was to determine the volumes and possibilities of production of certain types of meat products in Ukraine, their market share, prospects for production in the future, and the ability to provide food industry enterprises with raw materials for the production of new food products. The work was carried out by analysing scientific, regulatory and technical literature, statistical evaluation of data, and comparing the results obtained with the findings of other scientists. The analysis of the industry indicates the decline of certain areas in animal husbandry, in particular, cattle breeding and the production of meat, meat products from beef and veal; a decrease in the number of farm animals, namely by 23% of bovine cattle, 6.9% of pigs, and 2.4% of poultry. During the analysed period, poultry meat production increased by 17%, while the number of business entities increased by 25 %. At the same time, beef and veal production decreased by 27.8%, while pork production increased by 33%. Based on the results obtained, it is possible to continuously provide processing enterprises with meat raw materials, namely, chicken meat for the production of meat products, and it is also relevant to introduce resource-saving technologies for obtaining a product with less weight loss and waste during processing. The study results can be used by enterprises when planning the release of products to the market, developing new recipes, improving existing production technologies, and understanding trends and volumes of meat and meat products on the Ukrainian market